Aspects of reproductive biology of Drimys brasiliensis Miers (Winteraceae) in “floresta ombrófila mista”, south of Brazil Aspectos da biologia reprodutiva de Drimys brasiliensis Miers (Winteraceae) em floresta ombrófila mista, Sul do Brasil - Mariot A. (2014)
© 2014 Universidade Federal de Santa Maria. All rights reserved.Drimys brasiliensis Miers, locally known as “cataia” or “casca-de-anta”, is a native tree of “Floresta Ombrófila Mista”, in Brazil. Its bark has been used for medicine, through the exploitation of plants of natural populations. The present work aimed to study aspects of reproductive biology of Drimys brasiliensis in order to establish strategies for sustainable management and conservation, in order to generate alternative income from the exploitation of this non-timber forest product. Studies about reproductive phenology (296 plants during 2 years and a half), pollination and dispersal ecology, and floral biology were realized. The flowering season occurred the summer, with its peak in January. There are unripe fruits throughout the year, becoming ripe fruits as the temperature increases. There is a superposition of unripe and ripe fruit phenology from different flowering seasons. Ripe fruits are then, available for animals throughout the year. Hymenopteras are flower visitors with major potential for gene flow via pollen, but their frequency is low, like others flowers visitors, despite the high flowers production and pollen viability. Therefore, the highest fruit production which was seen comes from self-fecundation. The primary fruit dispersers are rare, birds being observed. However, the secondary dispersal of seeds that reach the ground by barocory is high.